Respuesta :

Answer: 3(p + 5) + 4(p + -2) = 4(p + 6)

Reorder the terms:

3(5 + p) + 4(p + -2) = 4(p + 6)

(5 * 3 + p * 3) + 4(p + -2) = 4(p + 6)

(15 + 3p) + 4(p + -2) = 4(p + 6)

Reorder the terms:

15 + 3p + 4(-2 + p) = 4(p + 6)

15 + 3p + (-2 * 4 + p * 4) = 4(p + 6)

15 + 3p + (-8 + 4p) = 4(p + 6)

Reorder the terms:

15 + -8 + 3p + 4p = 4(p + 6)

Combine like terms: 15 + -8 = 7

7 + 3p + 4p = 4(p + 6)

Combine like terms: 3p + 4p = 7p

7 + 7p = 4(p + 6)

Reorder the terms:

7 + 7p = 4(6 + p)

7 + 7p = (6 * 4 + p * 4)

7 + 7p = (24 + 4p)

Solving

7 + 7p = 24 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.

7 + 7p + -4p = 24 + 4p + -4p

Combine like terms: 7p + -4p = 3p

7 + 3p = 24 + 4p + -4p

Combine like terms: 4p + -4p = 0

7 + 3p = 24 + 0

7 + 3p = 24

Add '-7' to each side of the equation.

7 + -7 + 3p = 24 + -7

Combine like terms: 7 + -7 = 0

0 + 3p = 24 + -7

3p = 24 + -7

Combine like terms: 24 + -7 = 17

3p = 17

Divide each side by '3'.

p = 5.666666667

Simplifying

p = 5.666666667

HOPE THIS HELPS